Севастопольские рассказы: историческая лит-ра / Лев Толстой - Толстой Л. Н. (Вагриус, 2004)
Экземпляры: ф.7 (2004) / Инвентарный номер: 37478 / Цена: 42.18 / Авт.знак: Т 53 / ГРНТИ: 17.82.32 / ББК: Ш6(2=Р)5